Spatial distribution of relict charcoal hearths in the former royal forest district Tauer (SE Brandenburg, Germany). (30th March 2019) - Raab, A.; Bonhage, A.; Schneider, A.; Raab, T.; Rösler, H.; Heußner, K.-U.; Hirsch, F.
Abstract: Historical charcoal production has long been an unconsidered type of forest utilization in lowland areas. The archaeological discovery of a large charcoal burning area in the forefield of the active opencast lignite mine Jänschwalde in SE Brandenburg (North German Lowlands) has highlighted the need for multidisciplinary research in the study of the dimensions of historical charcoal burning. The charcoal produced in our study area, the former royal forest district Tauer, provided energy for the nearby Peitz ironworks during its operation from the mid-16th to the mid-19th century. Here, we aimed to record the amount, size and distribution of relict charcoal hearths (RCHs) to examine their context with respect to the ironworks and to better understand the potential impacts on late Quaternary landscape change. The applied methods combined archaeological research with shaded-relief mapping of RCHs. To evaluate the detection success of RCHs in the shaded-relief maps (SRMs), we compared the results with the results from specific archaeological surveys and conventional forest site mapping. Furthermore, we analyzed our dataset with descriptive, comparable and spatial statistics. Additionally, dendrochronological dating of charcoal fragments from selected RCHs was used to investigate the temporal relationships among the RCHs. Approximately 6000 circular RCHs were manually digitally identified in the SRMs of the 109-km 2 evaluable area. However, ground truthing showed that the shaded-relief maps could not completely capture all RCHs in our study area due to local conditions. At the regional scale, two focus areas with high RCH site densities were found. Statistical analysis revealed that the diameters of the RCHs range widely from 4 to 30.5 m. Spatial statistics were applied to the RCH diameters to aggregate areas with larger or smaller RCHs. At the small scale, no systematic arrangement of RCHs was obvious in the SRMs. Dendrochronological dating of selected RCHs lying close together could not detect significant spatiotemporal relationships or patterns. The dating results also showed that some areas have been preferentially used for charcoal production for over 300 years. Due to the homogeneity of the physio-geographical location factors, we assume that these factors are not superficially responsible for site selection. Instead, economic location factors and contemporary regulations are more likely responsible for the distribution of RCHs.